String Matching untuk Mendeteksi Serangan Sniffing (ARP Spoofing) pada IDS Snort - Ilham Firdaus; Januar Al Amien; Soni Soni (Jurnal CoSciTech (Computer Science and Information Technology), 2020)
Sniffing technique (ARP Spoofing) is an attack that sends fake ARP packets or ARP packets that have been modified according to the network address attacker's to poison the victim's ARP cache table. ARP spoofing attack is a dangerous attack because it can monitor the activities of victims in searching the browser and can steal social logins, office and other accounts. This attack supports the occurrence of other computer network attacks such as Denial of service, Man in the middle attack, host impersonating and others. Sniffing attacks are generally found in places that provide public Wi-Fi such as campus, libraries, cafes, and others. IDS Snort can detect sniffing attacks (Arp Spoofing). String Matching Method KMP algorithm is applied to detect attacks on snort logging files to provide alerts (messages) to users. Tests carried out are black box testing to test application functionality, and accuracy testing. All application functionality was successful, and testing the accuracy of the match between manual calculations for string matching and accurate application.